PERAWATAN PPE UNTUK MEMAKSIMALKAN USIA PAKAI STRUCTURAL FIREFIGHTING SUITS - Alfan Hugo; Lina Rosmayanti; Supri Supri (LPPM Politeknik Pratama, 2025)
This study aims to analyze the maintenance of Personal Protective Equipment (PPE), especially Structural Firefighting Suits (SFS), in an effort to maximize its lifespan at Kualanamu International Airport, Deli Serdang. Structural firefighting suits are essential protective equipment for Aviation Accident Rescue and Fire Fighting (PKP-PK) officers, which serve to protect personnel from the dangers of extreme temperatures and fire while on duty. However, suboptimal maintenance can lead to a decrease in the quality of protection and shorten the life of the equipment. This study identifies the various factors that influence the deterioration of suits, as well as the efforts that can be made to extend their lifespan, including the challenges faced in the maintenance process. Based on interviews with PKP-PK personnel and direct observation, it was found that factors causing damage include exposure to extreme temperatures, chemical contamination, and storage that is not in accordance with applicable standards. Efforts to extend the service life of suits include proper storage, regular cleaning with appropriate cleaning agents, and rotation of use to reduce wear and tear. In addition, the main challenges faced include budget constraints, inadequate storage facilities, and lack of systematic training for personnel. This study recommends the implementation of more standardized maintenance procedures, the development of Standard Operating Procedures (SOPs), as well as periodic training for personnel to extend the life of Structural Firefighting Suits and improve operational safety at Kualanamu International Airport. This study highlights the importance of standardized PPE maintenance as a critical step in strengthening occupational safety for aviation rescue and fire fighting operations.